Evaluation of the epidemiological profile and mortality of elderly with femur fracture residents in the state of Sergipe between january 2011 and december 2020 (Research, Society and Development, 2023)
Introduction Femur fracture in the elderly is a disease with significant morbidity and mortality and high incidence in Brazilian society. The main trauma mechanism is the accidental fall from own height and osteoporosis is the most important risk factor. Objective Define an epidemiological profile of elderly with femur fractures in the state of Sergipe. Methodology Descriptive, cross-sectional, quantitative study, based on the hospital admission system with data available on the DATASUS platform in the period between Jan/2011 and Dec/2020. Results An average annual incidence of 182/100,000 elderly was observed, this data showed an important growth with increasing age; regarding gender, there was a greater number of cases in females, with 2.17 more cases compared to males. There were 302 deaths in the period, with an average mortality rate of 7%. The average annual expenses corresponded of 885 thousand reais and average hospitalization time was about 12 days. Conclusion Femur fractures are quite common in the elderly population, with greater involvement in females, with a tendency to increase the number of cases over the years. A very high mortality rate was observed in the state, an alarming fact that highlights the need for more studies and improvement of public policies in the area to improve management and reduce morbidity and mortality.